Taxonomy of Trogon rufus (Gmelin, 1788) and Amazonian ring-shaped clinal variation - Dickens, Jeremy Kenneth (2015)
We reviewed the taxonomy of the Trogon rufus species-complex under the premises of the Biological Species Concept. Putative taxonomic units, breaks and transition zones, were visualised by heatmaps and isophenes (phenotypic contour lines) of the colour, barring, morphometric and song characters and tested by discriminant function analyses. Colourmetric data were obtained via spectrometry and barring patterns analysed via high quality digital photographs. We found four distinct biological species. Trogon chrysochloros Pelzeln 1856 from the Atlantic Forest with its denser and blacker undertail and wing covert barring, larger size and faster, generally higher song with more notes. Its upperparts vary from bluer to more coppery-green with increasing altitude. The bill is also relatively smaller and more serrated, linked to a diet that consists almost exclusively of large arthropods, making it the most insectivorous new world Trogon species yet known, which may account for its relative rarity compared to other Trogonids with which it is sympatric. Trogon tenellus Cabanis 1862, from Central America, and Trogon cupreicauda Chapman 1914 from the Chocó-Magdalena provide a classic case of typical biological species, coming into contact in the extreme NW Chocó Province, Colombia, but without intermediate forms. T. tenellus is identified by its blue to blue-green uppertail, blue or grey eye-rings, grey tarsi and song with 2-4 notes, longer note duration and greater change in peak and high frequencies between the intro note and loudsong. This contrasts with the shiny olive-green to coppery green uppertails, yellow eye-ring, usually olive tarsi, brown wash on the undertail of females and song with 6-8 notes of shorter duration and little change in frequency between the intro note and loudsong of T. cupreicauda. T. cupreicauda varies clinally from generally bluer- to more coppery-green plumage and from thicker to thinner black bars in a gradient from the Pacific coast on the border with Ecuador to the Magdalena Valley. The greater difference in colour and barring relative to T. tenellus in the region they come into contact provides possible evidence of character displacement as a result of the competitive exclusion between these two species, maintaining their parapatric distributions. The Amazonian population belongs to a single species, Trogon rufus Gmelin 1788, but with two highly distinct forms that we designate as Trogon rufus rufus in the Guiana Shield and Trogon rufus sulphureus in S & W Amazonia, for which Todd\'s amazonicus is synonymised. They are morphologically and, to a lesser extent, vocally distinct across the lower Rio Negro and matrix of highland and open habitats of the Rio Branco basin but show limited character exchange between the 52-58th parallels west on the southern bank of the Amazon, centred around the Rio Arapiuns on the left bank of mouth of the Tapajos. We postulate that this is the result of secondary contact as a consequence of shifts in the course of the main channel of the Amazon River at times of lower sea levels during the Plio-Pleistocene. T .r. sulphureus is identified by a typically coppery uppertail with subterminal tailband of greener hue, yellow eye-ring, low barring density and broad black bars of the undertail and wing-coverts barring with and lack of a pectoral band. They are also sometimes distinguishable in song by a higher frequency introduction note and/or more pronounced descending modulation across the loudsong. This varies clinally on a west-east gradient, from strong-coppery to shiny olive-green uppertails with more to less distinct subterminal tailbands, diminishing black bar widths with corresponding increasing density and decreasing intro note low frequency. T. r. rufus have green uppertails, blue eye-rings, presence or absence of a white pectoral band and denser undertail and wing panel barring with thinner black bars. These characters were shown to change as a function of geographic distance between specimens of sulphureus and rufus, connected via the \'Arapiuns contact zone\', suggesting isolation by distance. This is reminiscent of a ring species pattern and two specimens with a possible mixture of characters were indeed found from the upper Rio Negro and in Pantepui, where T. r. rufus and T. r. sulphureus would be expected to come into contact, effectively \'closing the ring\'. Whether Trogon rufus constitutes a valid ring species requires further testing, preferably including molecular characters, but this clearly illustrates that the distinction between clinal variation and ring-species is a matter of degree, not kind, with the formation of the ring-species necessarily passing through a clinal stage with no overlap between terminal taxa. We therefore propose the concept of a loop species, where the terminal forms do not overlap but are connected via a series of intergrading populations. It seems likely that such patterns are more widespread in Amazonia than presently known due to the propensity for clinal variation and parapatric speciation lended by its massive geographical extent and abundance of biogeographical semi-permeable barriers. With regards to the population from the Pernambuco Center of Endemism, the few records suggest that it is a valid taxonomic unit. It has the unique combination of a song very similar to T. r. sulphureus due to the high introduction note frequency and pronounced descent in frequencies across the loudsong, with a corresponding widening range but moderately large size, serrated bill and blue eye-ring but this certainly requires confirmation. This requires urgent attention, as the remnant population is very small and localised, recorded only from the Murici municipality, Alagoas.